Evaluation of a computer program for non-invasive determination of pulmonary shunt and ventilation-perfusion mismatch. - Lockwood, Geoffrey G; Fung, Nick L S; Jones, J Gareth (Journal of Clinical Monitoring & Computing, 2014)
We describe a three-compartment model (shunt and two perfused compartments) to analyse the relationship between inspired oxygen (FIO2) and arterial oxygen saturation (SaO2) in terms of pulmonary shunt and ventilation-perfusion ratio (VA/Q). The program was tested using 24 exact datasets, each with six pairs of FIO2 and SaO2 data points with known VA/Q and shunt, generated by a complex calculator of gas exchange. Additional datasets were created by adding noise and rounding the exact sets, and by reducing the number of data points per dataset. The importance of the oxyhaemoglobin dissociation curve and the arterio-venous difference in oxygen content (avDO2) were also tested. Analysis using the three compartment model was more accurate than the two compartment model and less affected by data degradation. The absolute error in shunt estimation was never more than 2.2 % for the exact and rounded datasets, but the error in VA/Q estimation was -29 to 19 % of the true value (10th-90th centiles). The characteristics of the well-ventilated compartment were not determined accurately. At extremes of cardiac output, an assumed value of avDO2 resulted in significant errors. It is probably advantageous to correct for foetal haemoglobin in neonatal datasets. Analysis of FIO2 versus SaO2 datasets using a three compartment model provides accurate estimates of shunt and VA/Q when arterio-venous difference in oxygen content is known. The estimates may have value as objective measures of gas exchange, and as a visual guide for oxygen therapy.